INDIRECT CEREBRAL REVASCULARIZATION ON OPTHALMIC ARTERY BY USING A DRUG-ELUTING BALLON FOR SUSPECTED MOYAMOYA DISEASE - Alwahdy, Ahmad Sulaiman; Usman, Fritz Sumantri (MNJ (Malang Neurology Journal), 2022)
Moyamoya disease (MMD) is a rare idiopathic progressive vaso-occlusive disease causing multiple occlusion of cerebral vessels lead to ischemic stroke. Asian population is the most common race to be affected. We present a male patient 33-years old with suspected MMD with right hemiparesis and neurocognitive changes. On digital substraction angiography (DSA) there was appearance of ‘puff of smoke’ on his right hemisphere, stenosis middle cerebral arteries M1 bilaterally, stenosis of right opthalmic artery (OA), stenosis of left anterior cerebral artery (ACA) and aplasia of right ACA. Ballon angioplasty was performed on right OA that supply the contralateral symptomatic stenosis area (left A1) indirectly through anterior ethmoidal artery and anterior falcine artery (OA-ACA collateral). While no guidelines for the management of MMD, cerebral revascularization by using drug-eluting ballon (DEB) in right opthalmica artery is potentially effective treatment  that could allow the brain to have good blood supply (gives good collateral to both ACA), reduces burden of the fragile moya-moya vessels to be ruptured followed by  improvement of clinical results. Patient’s selection by understanding the stage, its progressivity and collateral formation are crucial before decision is made.